Analisis Penerapan Standar Akuntansi Keuangan Entitas Tanpa Akuntabilitas Publik (SAK ETAP) Dalam Pengajian Laporan Keuangan - Sutarti, Sutarti; Djanegara, Moermahadi Soerja; Handono, Aldy Dwi (Institut Bisnis dan Informatika Kesatuan, 2015)
The purpose of this study was to analyse the application of SAK ETAP inconjunction with the presentation of financial statements in the PDAM Tirta Pakuan Kota Bogor. The analysis is perfomed to determine how financial statements of PDAM Tirta Pakuan are already in accordance with SAK ETAP. The analysis conducted in this study using a descriptive qualitative method while selected data sources are secondary data from financial statements. The selected data collection procedures are literatures and records, field research and interview. The results showed that the cooperative PDAM Tirta Pahcan Kota Bogor has been making adjustments in applying SAK ETAP in the presentation of financial statements, but still not all the adjustments in the SAK ETAP has been applied in the presentation offinancial statements consisting of a balance sheet, profit/loss, change in equity, and cash flow statements. Cooperative PDAM Tirta Pakuan Kota Bogor using SAK ETAP with reporting guidelines are still largely the same as before adopting IFRS GAAP. In general, there are not many significant changes occured. In other words, there was no significant effect happens on the application of GAAP in the financial statements cooperative SAK ETAP PDAM Tirta Pakuan Kota Bogor. Keyword : SAK ETAP, Presentation of Financial Statements